(untitled) (Journal of the College of Education for Women, 2019)
It is a well-known fact that publishing companies spend much money, time and energy in designing their book covers to attract potential customers. As the first thing people do when they buy or intend to buy a book is looking at its front cover. However, if there is a need to know more about the book, people usually look at the information on its back cover. This paper attempts to explore the persuasive function of blurbs beyond the constraints of the academic domain and consequently their connection with advertising discourse in two main sections: The first presents the concept of blurb and its structure while the second defines persuasion and shows the most prominent strategiesused in blurbs. Finally, this paper gives the conclusion that the blurb is a persuasive text as it aims to influence others to buy the book and therefore, blurb is a type of advertising.